Comparison and determination of properties of oil extracted using soxhlet and supercritical fluid from Nile tilapia (Oreochromis niloticus Linnaeus) processing waste - Khazaali, Masoumeh (2016)
Fish oil contains the important omega-3 polyunsaturated fatty acids (PUFAs), Eicosapentaenoic acid (EPA) and Docosahexaenoic acid (DHA). EPA and DHA extracted from fish oil are reported to have beneficial effects to human health which resulted in a world-wide demand. There are already several methods available for extracting fish oil, with varying degrees of yield and quality. Supercritical fluid carbon dioxide extraction (SFE-CO2) is an emerging process for the extraction of edible oils containing labile components like PUFAs. Therefore, the objectives of this study were (i) to extract and compare the distribution of oil and physicochemical properties of tilapia oil extracted from the viscera, head, skin and flesh using the soxhlet and supercritical fluid methods; (ii) to optimize the yield and extracted EPA and DHA from the identified part using supercritical fluid extraction (SFE-CO2) technique. The results from the soxhlet method revealed that the distribution of oil was significantly (p < 0.05) different among the head, viscera, skin and flesh which is as expected. The highest oil yield was obtained from the viscera (51.81%) followed by the head (30.12%), skin (16.88%) and flesh (6.78%). The chemical properties of head, viscera, flesh and skin oil were 4.37-9.87 meq O2/kg, 116.94- 125.65 g I2/100 g, 4.49-9.86 meq/kg and 13.23-25.08 meq/kg for PV, IV, p-AnV and TOTOX value, respectively. Although the average fatty acids composition of the viscera, head, skin and flesh samples were similar, the highest amounts of SFAs (49.74 g/100 g oil), MUFAs (24.40 g/100 g oil) and PUFAs (22.14 g/100 g oil) were found in the flesh, viscera and head, respectively. The optimization of oil yield, extraction of EPA and DHA based on central composite design with pressure (20-40 MPa), temperature (35-75 °C), flow rate (2.5-4.5 mL.min−1) and extraction time (2-4 h) from the viscera was determined. The highest oil yield (40.02% on dry weight basis), EPA (0.46 g/100 g oil) and DHA (1.53 g/100g oil) was obtained at 40 MPa, 57.22 °C, 3.4 mL.min−1 and 3.23 h with non-significant (p > 0.05) lack of fit and high R2 (p > 0.90). The viscera oil from supercritical fluid extraction (SFE-CO2) had lower total oxidation value (15.3 meq/kg) and higher amount of PUFAs composition (28.71 g/100 g oil) than oil obtained from soxhlet method (25.08 meq/kg and 17.32 g/100 g oil for TOTOX value and PUFAs, respectively). Hence, tilapia visceral oil is better extracted using supercritical fluid extraction method.